Incorporating DRAGON12-light trainer board in an introductory microprocessors course - Shadi Alawneh (Springer, 2024)
Abstract The HCS12 microcontroller and DRAGON12-Light Trainer boards are extensively utilized in microprocessor system design education. This paper details the rationale, approach, and outcomes from implementing the DRAGON12-Light Trainer board in teaching an upper-level undergraduate microprocessors course at Oakland University. The course's primary goal is for students to acquire the skills necessary to design both hardware and software for microprocessor-based systems, with applications across various industries. The paper assesses the effectiveness of employing the Motorola HCS12 microcontroller for its real-world relevance and integrates the Freescale CodeWarrior IDE v5.1 environment for software development. This research uniquely contributes by measuring the improvement in students' practical skills, specifically in hardware and software design using assembly and C programming, through hands-on lab assignments. It reports on the development of students' abilities to engage in microprocessor-based system design and critically evaluates the applied aspects of pedagogy by incorporating the DRAGON12-Light Trainer in lab exercises, such as those involving 'Measuring Human Reaction Time' and 'Servo motor interfacing.' Quantitative results, derived from student surveys and assessments, indicate significant improvements in students' programming competencies. The paper provides statistical results showcasing the increase in students' self-rated confidence levels in assembly and C language programming before and after course completion. Additionally, qualitative insights are discussed, reflecting students' experiences and the perceived applicability of the skills they acquired. These results underscore the pedagogical value of integrating practical training devices like the DRAGON12-Light Trainer board into microprocessors curricula.